Metabolic and endocrine responses to hypoxic exposure - Goto, K. (The Journal of Physical Fitness and Sports Medicine, 2013)
A growing body of evidence suggests that exposure to hypoxic conditions during rest and exercise may be beneficial for the prevention of metabolic syndrome. Epidemiologic studies indicated that mortality rates from coronary heart disease were lower in populations living at higher altitudes than for those living at lower altitudes. Recent researches demonstrated that exercise training conducted under hypoxic conditions resulted in further reduction of body fat mass, greater improvement of postprandial glycemic control compared with the effects of similar exercise training conducted under normoxic conditions. In particular, the findings strongly suggest that augmented glucose metabolism resulting from exposure to hypoxic conditions is a pronounced advantage. Additionally, moderate hypoxic exposure further improves insulin sensitivity and glycemic regulations when exercise is combined. A further benefic of hypoxic training appears to be a reduction of appetite. Altered regulation of appetite-related hormonal responses might be a key to understanding the mechanisms of weight loss at high altitude stay and/or exercise.